Pengaruh Kualitas Pelayanan Dan Harga Terhadap Keputusan Pembelian Pada Konsumen Dan+Dan Walang Baru Jakarta Utara - Krishantoro, Krishantoro; Mawarni, Mega (JAMBIS : Jurnal Administrasi Bisnis, 2023)
This study aims to determine how much influence Service Quality and Price have on Purchasing Decisions at Dan+Dan Walang Baru, North Jakarta. The research method used is a quantitative method. The data collection technique is in the form of a questionnaire. The population in this study is anyone who comes to shop for the first time and who has come to shop more than 2 times at Dan+Dan Walang Baru. The sampling technique for this study used purposive sampling, namely consumers who came to shop for the first time and who had come to shop more than 2 times at Dan+Dan Walang Baru. This study shows that the results of the coefficient of determination of the R Square value of Service Quality is 0.506 which indicates that the variable Service Quality influences purchasing decisions by 50.6%. The results of the coefficient of determination for the R Square value of Price is 0.373 which indicates that the Price variable influences the Purchase Decision by 37.3%. The results of the coefficient of determination of the R Square value of Service Quality and Price are 0.567 which indicates that the variables Service Quality and Price have a joint effect on Purchasing Decisions of 56.7%, while the remaining 43.3% are influenced by other variables not examined in this study.